Designing of an anti-rutting and High Ductility Asphalt Mixture based on mortar performance. (17th January 2022) - Nie, Guihai; Cai, Xu; Huang, Wenke; Hassan, Hafiz Muhammad Zahid; Chen, Sihang; Zhang, Qiran; Xie, Jiawen; Wu, Kuanghuai
Highlights: The variation laws of mortar indicators were investigated by performance tests. The correlation between mortar performance and mixture performance was analyzed. Mixture with excellent anti-rutting and deformation performance was designed. The design method can realize the coordination of rutting and crack resistance. Abstract: The anti-rutting and anti-cracking performance of asphalt mixtures are a pair of contradictions that are difficult to coordinate. In order to ensure the rutting resistance of asphalt mixture to meet the requirements of the specification, while improving its deformation capacity and crack resistance. Based on the mortar performance, the Anti-rutting and High Ductility Asphalt Mixture with excellent anti-rutting performance and deformation performance was designed in this paper. With the filler-asphalt ratio as the control index, SBS modified asphalt and SHV modified asphalt was selected to design five asphalt mortars with different filler-asphalt ratios of 0, 0.5, 1.0, 1.5, 2.0. Variation laws of mortar technical indicators were investigated by rotational viscosity test, cone penetration test, and BBR test. Asphalt mixtures were prepared and a rutting test and small beam bending test were carried out to ensure the consistency of the mixture skeleton state by grouting molding. The influence of the mortar performance index on the road performance of the mixture was evaluated by conducting correlation analysis, and then an anti-rutting and high-ductility asphalt mixture was proposed based on mortar performance. The obtained results showed that the technical indicators of asphalt mortar had a good correlation with the filler-asphalt ratio, and the developed regression model could be used to determine the correlation and design of the mortars. The technical performance index of mortar was found to be directly correlated with the road performance index of the mixture. The developed anti-rutting and high-ductility asphalt mixture not only had good anti-rutting performance but also had good deformation capacity and cracking resistance. Its anti-rutting performance could meet the specification requirements, and the maximum flexural strain could reach 7161 με. The performance of asphalt mortar determines the road performance of the mixture. The rutting resistance and cracking resistance of the mixture could be coordinated by designing asphalt mortar to improve its comprehensive road performance. To guarantee that the dynamic stability of the mixture met the required specifications and the deformation ability was good, the critical value of each technical index of asphalt mortar was recommended.